Controlling and assessing the quality of aerosol jet printed features for large area and flexible electronics. (28th February 2017) - Smith, Michael; Choi, Yeon Sik; Boughey, Chess; Kar-Narayan, Sohini
Abstract: Aerosol jet printing (AJP) is a versatile technique suitable for large-area, fine-feature patterning of both rigid and flexible substrates with a variety of functional inks. In particular, AJP can tolerate ink viscosities between 1 and 1000 cP, with printing resolution of the order of 10 μ m, thus making it attractive for flexible and printed electronics. This work investigates in detail significant aspects of ink-substrate combination and substrate temperature that are highly relevant to AJP. In order to do this, thin conducting silver lines are printed using AJP on both rigid (glass and silicon) as well as flexible (polyimide) substrates. The correlation between the various deposition parameters and the 'quality' of the printed lines are evaluated, through measurements of electrical conductivity under different experimental conditions. Based on our findings, a framework is proposed through which the morphology of AJP lines can be controlled and assessed for applications in large area and flexible electronic devices.